Nickel ferrite composite material magnetized cellulose flocculant, and preparation method and application thereof

CN120024981BActive Publication Date: 2026-10-27ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510444852.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2026-10-27
Estimated Expiration
2045-04-10

AI Technical Summary

Technical Problem

而印染废水pH波动大(强酸或强碱),需额外调节pH,增加处理成本和复杂性

Benefits of technology

[0030](1)本发明提供的镍铁氧体复合材料磁化纤维素絮凝剂主要原料纤维素、硅烷偶联剂,氯化铁六水合物和氯化镍六水合物来源广泛,价格低廉;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120024981B_ABST
    Figure CN120024981B_ABST
Patent Text Reader

Abstract

The application discloses a kind of ferrite composite material magnetized cellulose flocculants and its preparation method and application, the flocculant with microcrystalline cellulose, ferrite and silane coupling agent as main raw material, cellulose is oxidized by NaIO4, ammonium gasification and NaBH3CN reduction modification and is obtained with the amine cellulose of surface modification-OH and-NH2, Fe salt and Ni salt coprecipitation form NiFe2O4 Particle, and through sol-gel method, SiO2 Layer is coated;Finally by silane coupling agent, NiFe2O4@SiO2 It is grafted to the surface of amine cellulose, and forms composite flocculant.The preparation process of the application is simple, reaction condition is mild, raw material cost is low, and it has the magnetism of inorganic material and the adsorption of organic material, realizes synergistic effect.Application in printing and dyeing wastewater treatment, the removal effect of COD, total lead and color is remarkable, under the best condition, COD removal rate reaches 74.56%, total lead removal rate reaches 91.53%, and color removal rate reaches 90.62%, which is superior to traditional flocculant (such as polymeric ferric sulfate), the flocculant is wide in pH range, and the dosage is low (1.5g / L).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment technology, specifically relating to a nickel ferrite composite magnetized cellulose flocculant, its preparation method, and its application. Background Technology

[0002] With the rapid development of the dyeing and printing industry, wastewater discharge during the dyeing and printing process releases many pollutants, such as dyes, auxiliaries, heavy metals, and acidic and alkaline organic matter. This wastewater is characterized by high color, high organic content, complex composition, poor biodegradability, and unstable treatment effects. In China, dyeing and printing wastewater treatment methods are diversified, encompassing biological, chemical, and physical methods. Among them, chemical coagulation has stood out and is widely favored and applied in the field of dyeing and printing wastewater treatment. This method is highly adaptable, flexibly responding to various complex and changing wastewater qualities and fully utilizing its effectiveness. The operation process is simple and easy to implement, requiring no professional personnel to spend a lot of time on complex operations, greatly reducing labor costs and technical barriers. It occupies relatively limited space, effectively solving the problem of limited space for enterprises. In terms of treatment effect, chemical coagulation performs excellently, with high removal efficiency for chemical oxygen demand (COD) and color, significantly reducing the pollution level of dyeing and printing wastewater and minimizing the pressure on subsequent treatment. It meets the needs of dyeing and printing enterprises from multiple dimensions, contributing to the sustainable development of the dyeing and printing industry. However, existing technologies for treating dyeing and printing wastewater using flocculants face many technical challenges. Dyes in this wastewater (such as reactive and disperse dyes) typically possess complex organic structures and high stability, making it difficult for traditional flocculants to effectively break their chemical bonds, resulting in low decolorization efficiency, especially for soluble dyes. Furthermore, most flocculants (such as aluminum and iron salts) require a specific pH range to achieve optimal results. Dyeing and printing wastewater, however, exhibits significant pH fluctuations (strong acids or strong alkalis), necessitating additional pH adjustments and increasing treatment costs and complexity.

[0003] Cellulose possesses the characteristics of being a renewable raw material, having low toxicity, low density, high crystallinity, high surface area, good mechanical strength, insolubility in water, and biodegradability. Due to its abundant hydroxyl groups, long-chain molecular structure, and physical stability resulting from chemical stability, as well as its rich adsorption active sites, high adsorption capacity, and binding affinity, it has potential application value in the treatment of dyeing and printing wastewater.

[0004] Silane coupling agents can couple organic and inorganic materials, improving the mechanical strength of the product. Nickel ferrite has an inverse spinel structure, thus exhibiting good chemical stability, mechanical toughness, and moderate saturation magnetization. Its acid resistance can usually be improved by forming a silicon layer. The resulting nickel ferrite composite material has good hydrothermal stability and is fully biodegradable, indicating its potential adsorption treatment performance in practical applications. Summary of the Invention

[0005] The purpose of this invention is to provide a novel nickel-ferrite composite magnetized cellulose flocculant, its preparation method, and its application in removing COD, total lead, and color from dyeing and printing wastewater.

[0006] The technical solution adopted in this invention is:

[0007] A nickel-ferrite composite magnetized cellulose flocculant, comprising the following components:

[0008] Amine cellulose matrix: prepared by oxidation of cellulose with NaIO4, ammonia amination and reduction modification with NaBH3CN, and the surface is modified with hydroxyl-OH and amino-NH2 functional groups;

[0009] NiFe2O4@SiO2, a nickel ferrite composite material, is formed by synthesizing NiFe2O4 from Fe salt and Ni salt under alkaline conditions via co-precipitation and then coating it with a SiO2 layer using a sol-gel method.

[0010] Silane coupling agent bridging structure: The aminated cellulose matrix and NiFe2O4@SiO2 are covalently linked by 3-glycidyl etheroxypropyltrimethoxysilane KH560 to form an organic-inorganic hybrid network, which is the flocculant.

[0011] Furthermore, the mass ratio of the aminated cellulose to NiFe2O4@SiO2 is 2:1 to 1:1.

[0012] Furthermore, the mass ratio of the aminated cellulose to NiFe2O4@SiO2 is 4:3.

[0013] A method for using the nickel ferrite composite magnetized cellulose flocculant includes the following steps:

[0014] (1) Cellulose oxidative amination:

[0015] Cellulose was dispersed in softened water, NaIO4 solution was added, and the mixture was stirred at 50-60°C for 6-8 hours. After filtration and washing, oxidized cellulose was obtained.

[0016] Oxidized cellulose was mixed with 37% ammonia water at a solid-liquid ratio of 1g:10-20mL, and NaBH3CN solution was added. The mixture was reacted at 70-95℃ for 12-15h. During the reaction, the mixture was cooled and refluxed to prevent ammonia from evaporating, thus obtaining amination cellulose.

[0017] (2) Preparation of NiFe2O4@SiO2:

[0018] Trivalent Fe salt and divalent Ni salt were mixed in a molar ratio of 2 to 4:1 and coprecipitated in an aqueous solution of NaOH with a final concentration of 0.7-1.0 mol / L at room temperature for 0.5-2 h. After that, NiFe2O4 was obtained by centrifugation and washing.

[0019] NiFe2O4 was dispersed in ethanol, ammonia and tetraethyl orthosilicate (TEOS) were added, and the mixture was stirred at 50-60℃ for 20-24 h to carry out the hydrolysis reaction of TEOS and coat the NiFe2O4 with a SiO2 layer. After centrifugation and washing, NiFe2O4@SiO2 was obtained after high-temperature calcination.

[0020] (3) Flocculant compound:

[0021] Aminated cellulose was dissolved in toluene, and KH560 and NiFe2O4@SiO2 were added. The mixture was heated under reflux for 10-15 hours. After filtration, washing, and drying, the target flocculant was obtained.

[0022] Furthermore, in step (1), the mass ratio of NaIO4 to cellulose is 0.2-0.4:1, and the mass ratio of NaBH3CN to oxidized cellulose is 0.05-0.1:1.

[0023] Furthermore, in step (2), the final concentration of ammonia in the TEOS hydrolysis reaction system is 4-8%, and the feed ratio of NiFe2O4 to TEOS is 8-12g:1mL.

[0024] Furthermore, in step (3), the mass ratio of KH560 to aminated cellulose is 0.8-1.2:1, and the mass ratio of aminated cellulose to NiFe2O4@SiO2 is 1-2:1, preferably 4:3.

[0025] Furthermore, the calcination temperature in step (2) is 700-800℃, and the heating temperature in step (3) is 70-80℃.

[0026] The present invention also discloses the application of the flocculant in the treatment of dyeing and printing wastewater. The pH of the wastewater is 5-11, the dosage of the flocculant in the wastewater is 1.0-2.0 g / L, the treatment temperature is room temperature, the reaction time is 30-60 min, and the removal rates of COD, total lead and color are ≥70%, 85% and 85%, respectively.

[0027] Furthermore, the initial COD of the dyeing and printing wastewater is ≤3000mg / L, the color is ≤2000 times, and the total lead concentration is ≤2.0mg / L.

[0028] Cellulose contains numerous hydrogen bonds and hydroxyl groups on its surface. This hydrogen bond network gives cellulose high strength and toughness, as well as strong hydrophilicity, making it readily adsorbable of polar pollutants. Hydrogen bonds can form between the surface hydroxyl groups and polar groups in dye molecules, as well as organic auxiliaries. This intermolecular force allows reactive dye molecules to firmly bind to the cellulose surface, thereby removing color from wastewater. The large number of hydroxyl groups can be functionalized to introduce more materials to improve its adsorption performance. After acidification, the hydrogen bonds between two adjacent aldehyde groups in cellulose break, forming two aldehyde groups. Following amination, these two adjacent aldehyde functional groups transform into -OH and -NH2. Due to the nucleophilic reaction, the nucleophilic electrons on the amino group attack the epoxy group on the added 3-glycidyl etheroxypropyltrimethoxysilane, causing the epoxy group to open the ring and form -NH-C, which is then grafted onto the cellulose. The introduced -NH- groups can be protonated in dyeing and printing wastewater, thus carrying a positive charge. This charge neutralizes the negatively charged colloidal particles in the wastewater through electrostatic interactions, reducing interparticle repulsion, promoting aggregation, and improving flocculant treatment efficiency. Under alkaline conditions, Ni 2+ and Fe 3+ NiFe₂O₄ particles are generated through ion co-precipitation. A Si-O-Si framework structure is formed by the hydrolysis and condensation of tetraethyl silicate using a sol-gel method. This framework can encapsulate the Si-OH groups generated on the surface of the NiFe₂O₄ particles, which can form Si-O-Si bonds with the methoxy groups on 3-glycidyl etheroxypropyltrimethoxysilane. This connects NiFe₂O₄@SiO₂ to cellulose. The hydroxyl groups on the surface can form hydrogen bonds with polar groups in dyes, achieving adsorption. Furthermore, the metal sites on the surface of NiFe₂O₄@SiO₂ adsorb heavy metal ions through coordination. A nickel-ferrite composite magnetized cellulose flocculant is thus prepared. Experiments show that this invention has excellent treatment effects on removing COD, total lead, and color from dyeing and printing wastewater.

[0029] The beneficial effects of this invention are mainly reflected in:

[0030] (1) The main raw materials of the nickel ferrite composite magnetized cellulose flocculant provided by the present invention, namely cellulose, silane coupling agent, ferric chloride hexahydrate and nickel chloride hexahydrate, are widely available and inexpensive.

[0031] (2) The method for preparing nickel ferrite composite magnetized cellulose flocculant provided by the present invention is simple to operate, has mild reaction conditions, and low energy consumption.

[0032] (3) The nickel ferrite composite magnetized cellulose flocculant provided by the present invention combines inorganic and organic components by grafting, giving full play to the synergistic effect of inorganic and organic flocculants. It has high stability and a wider pH range of applicability.

[0033] (4) The quaternary ammonium introduced on the surface of cellulose provided by the present invention can be protonated to carry a positive charge, and neutralize the negatively charged pollutants in wastewater through electrostatic interaction; at the same time, hydroxyl groups are introduced to form hydrogen bonds with dye molecules, thereby enhancing color removal.

[0034] (5) The nickel ferrite composite magnetized cellulose flocculant provided by the present invention modifies the functional groups of cellulose, thereby introducing a large number of hydroxyl functional groups and NiFe2O4@SiO2 materials on the surface of cellulose, which improves the removal effect of cellulose on COD, total lead and color in water. Attached Figure Description

[0035] Figure 1 The image shows the scanning electron microscope (SEM) image of the magnetized cellulose flocculant in the nickel ferrite composite material obtained in Example 1.

[0036] Figure 2 The graph shows the effect of flocculant dosage and COD, total lead and color removal in dyeing and printing wastewater in Example 1 of the present invention.

[0037] Figure 3 The diagram shows the reaction time and the removal effects of COD, total lead, and color in wastewater in Example 1 of the present invention. Detailed Implementation

[0038] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0039] The cellulose used in this embodiment of the invention was purchased from Shanghai Haohong Biomedical Technology Co., Ltd., and its particle size was 20-80 μm.

[0040] Example 1

[0041] A method for preparing a novel nickel-ferrite composite magnetized cellulose flocculant includes the following steps:

[0042] Step 1: Weigh 10g of cellulose with a particle size of 20-80μm, add it to 130mL of softened water and mix. Add 20mL of 0.8mol / L NaIO4 solution, maintain the temperature at 50℃, stir at 400rpm and magnetically stir for 6h. Then stir at room temperature for 2h. Filter the mixture under vacuum, wash the resulting filter cake with deionized water and then vacuum dry to obtain oxidized cellulose.

[0043] Step 2: Add 10g of oxidized cellulose to a 37% ammonia solution at a solid-liquid ratio of 1g:10mL. Maintain the heating temperature at 75℃ and stir for 3h. Set the cooling reflux to prevent ammonia evaporation. Continue to add 50mL of a 0.2mol / L NaBH3CN / ethanol mixed solution. Maintain the heating temperature at 95℃ and stir for 15h with cooling reflux. Stir at 280rpm. Then, remove the solvent by rotary evaporation to obtain aminated cellulose.

[0044] Step 3: Mix 160 mL of 1 mol / L FeCl3·6H2O aqueous solution and 40 mL of 1 mol / L NiCl2·6H2O aqueous solution, stir at room temperature for 0.5 h, add the mixture to 500 mL of 1 mol / L sodium hydroxide aqueous solution, continue stirring at room temperature for 1 h, wash with deionized water and centrifuge to obtain NiFe2O4.

[0045] Step 4: Disperse 9g of NiFe2O4 precipitate in 25mL of ethanol, sonicate at 20kHz and 60℃ for 2h, add 10mL of 25% ammonia and 1mL of 98% tetraethyl silicate reagent, stir magnetically at 60℃ and 400rpm for 20h, then centrifuge, wash three times with 15mL of methanol, vacuum dry for 48h, and calcine at 800℃ for 2h to obtain NiFe2O4@SiO2 particles.

[0046] Step 5: Dissolve 10g of aminated cellulose material in 50mL of toluene solution, add 10mL of 98% 3-glycidyl etheroxypropyltrimethoxysilane, and add NiFe2O4@SiO2 particles at a mass ratio of 2:1 (aminated cellulose material to NiFe2O4@SiO2 particles). Heat and reflux at 80℃ for 13h.

[0047] Step 6: Filter the product obtained in step (5), wash with 50 mL of toluene, and dry under vacuum to obtain the nickel ferrite composite magnetized cellulose flocculant Y1. SEM image of flocculant Y1 is shown below. Figure 1 .

[0048] Example 2

[0049] A novel method for preparing a nickel ferrite composite magnetized cellulose flocculant is disclosed. The preparation steps are repeated in Example 1, except that in step 5, the amount of NiFe2O4@SiO2 particles is changed so that the mass ratio of aminated cellulose material to NiFe2O4@SiO2 particles is adjusted to 4:3. All other conditions remain unchanged, and the nickel ferrite composite magnetized cellulose flocculant Y2 is finally obtained.

[0050] Example 3

[0051] A novel method for preparing a nickel ferrite composite magnetized cellulose flocculant is disclosed. The preparation steps are repeated in Example 1, except that in step 5, the amount of NiFe2O4@SiO2 particles is changed so that the mass ratio of aminated cellulose material to NiFe2O4@SiO2 particles is adjusted to 1:1. All other conditions remain unchanged, and the nickel ferrite composite magnetized cellulose flocculant Y3 is finally obtained.

[0052] Example 4

[0053] A method for preparing a novel nickel ferrite composite magnetized cellulose flocculant is described. The preparation steps are repeated in Example 1, except that in step 2, the solid-liquid ratio of oxidized cellulose to 37% ammonia is adjusted to 1g:15mL. All other conditions remain unchanged, and the nickel ferrite composite magnetized cellulose flocculant Y4 is finally obtained.

[0054] Example 5

[0055] A method for preparing a novel nickel ferrite composite magnetized cellulose flocculant is described. The preparation steps are repeated in Example 2, except that in step 2, the solid-liquid ratio of oxidized cellulose to 37% ammonia is adjusted to 1g:15mL. All other conditions remain unchanged, and the nickel ferrite composite magnetized cellulose flocculant Y5 is finally obtained.

[0056] Example 6

[0057] A method for preparing a novel nickel ferrite composite magnetized cellulose flocculant is described. The preparation steps are repeated in Example 3, except that in step 2, the solid-liquid ratio of oxidized cellulose to 37% ammonia is adjusted to 1g:15mL. All other conditions remain unchanged, and the nickel ferrite composite magnetized cellulose flocculant Y6 is finally obtained.

[0058] Example 7

[0059] A novel method for preparing magnetized cellulose flocculant from nickel ferrite composite material is described. The preparation steps are repeated in Example 1, except that in step 2, the solid-liquid ratio of oxidized cellulose to 37% ammonia is adjusted to 1g:20mL. All other conditions remain unchanged, and the magnetized cellulose flocculant Y7 from nickel ferrite composite material is finally obtained.

[0060] Example 8

[0061] A novel method for preparing magnetized cellulose flocculant of nickel ferrite composite material is disclosed. The preparation steps are repeated in Example 2, except that "in step 2, the solid-liquid ratio of oxidized cellulose to 37% ammonia is adjusted to 1g:20mL", and the other conditions remain unchanged. Finally, magnetized cellulose flocculant Y8 of nickel ferrite composite material is obtained.

[0062] Example 9

[0063] A novel method for preparing magnetized cellulose flocculant from nickel ferrite composite material is described. The preparation steps are repeated in Example 3, except that in step 2, the solid-liquid ratio of oxidized cellulose to 37% ammonia is adjusted to 1g:20mL. All other conditions remain unchanged, and the magnetized cellulose flocculant Y9 from nickel ferrite composite material is finally obtained.

[0064] Comparative Example 1

[0065] The flocculant was cellulose, which was purchased from Shanghai Haohong Biomedical Technology Co., Ltd.

[0066] Comparative Example 2

[0067] The flocculant was NiFe2O4@SiO2 prepared in step 4 of Example 1.

[0068] Comparative Example 3

[0069] The preparation method of the flocculant in Comparative Example 3 was the same as that in Example 1, except that the NaIO4 solution in step 1 was replaced with an equimolar concentration of HCl solution, and the other conditions remained unchanged, and the flocculant was obtained.

[0070] Comparative Example 4

[0071] The flocculant was polyferric sulfate, purchased from Henan Zhongbang Environmental Protection Technology Co., Ltd.

[0072] Comparative Example 5

[0073] The flocculant was polyaluminum ferric silicate, purchased from Zibo Guangzheng Aluminum Salt Chemical Co., Ltd.

[0074] Comparative Example 6

[0075] The flocculant was polyaluminum chloride, purchased from Zhengzhou Daqian Environmental Protection Technology Co., Ltd.

[0076] Comparative Example 7

[0077] The flocculant was polyacrylamide, purchased from Sichuan Shuiyuanqing Environmental Protection Technology Co., Ltd.

[0078] Application Example 1:

[0079] Wastewater from a printing and dyeing factory in Zhejiang Province was used. The wastewater in the production process had a pH of 6.5, a COD content of approximately 2800 mg / L, a total lead content of approximately 1.12 mg / L, and a color of approximately 1500.

[0080] The flocculant Y1 prepared in Example 1 was added to wastewater at dosages of 0.5 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, and 2.5 g / L, respectively. 1 L of wastewater was treated according to these different flocculant dosages at a temperature of 25°C and a reaction time of 60 min. The treatment effects on COD, total lead, and color in the water are shown in Table 1. Figure 2 As shown.

[0081] Table 1

[0082]

[0083] The flocculant Y1 prepared in Example 1 was added to wastewater at a dosage of 1.5 g / L to treat 1 L of wastewater at a temperature of 25°C. The treatment effects on COD, total lead, and color in the water at different reaction times (10 min, 20 min, 30 min, 40 min, 50 min, and 60 min) are shown in Table 2. Figure 3 As shown.

[0084] Table 2

[0085]

[0086]

[0087] As can be seen from Table 2, the treatment effect of the flocculant first increases and then decreases with the increase of treatment time. This is because the flocs loosen due to prolonged static state, and some fine particles are resuspended, and then tend to stabilize.

[0088] The flocculant prepared in Example 1 and the flocculants of Comparative Examples 1, 2, 3, 4, 5, 6, and 7 were all added to wastewater at a dosage of 1.5 g / L to treat 1 L of wastewater at a temperature of 25°C and a reaction time of 40 min. The effects on COD, total lead, and color in the wastewater were shown in Tables 3, 4, and 5 when the pH of the wastewater was adjusted to 5, 7, 9, and 11, respectively.

[0089] Table 3 shows the removal efficiency of COD from wastewater.

[0090]

[0091]

[0092] Table 4 shows the removal efficiency of total lead in wastewater.

[0093]

[0094]

[0095] Table 5 shows the effect of removing color from wastewater.

[0096]

[0097] The flocculants prepared in Examples 1-9 and Comparative Examples 1, 2, 3, 4, 5, 6, and 7 were each added at 1.5 g / L to 1 L of wastewater. The reaction was carried out at 25 °C for 40 min. The effects on COD, total lead, and color in the wastewater are shown in Table 6.

[0098] Table 6

[0099]

[0100]

[0101] according to Figure 1 and Figure 2 It can be seen that the flocculant prepared in Example 1, at pH=6.5, has a COD content of approximately 2800 mg / L, a total lead content of approximately 1.12 mg / L, and a color of approximately 1500. The optimal dosage of the flocculant in dyeing and printing wastewater is 1.5 g / L, and the optimal reaction time is 40 min. Analysis of orthogonal experimental data shows that for COD, total lead, and color removal, a higher proportion of nickel-ferrite composite material in the magnetized cellulose flocculant is not necessarily better; the optimal ratio is 4:3, and a solid-liquid ratio of cellulose to ammonia of 1:15 allows for sufficient amination.

[0102] Compared with the comparative examples, the nickel-ferrite composite magnetized cellulose flocculant prepared in the examples, through cellulose amination and grafting with nickel-ferrite iron via organosilicon covalent bonds using a silane coupling agent, modifies the cellulose surface to generate a large number of hydroxyl groups and introduces them into the nickel-ferrite iron composite material, exhibiting good removal effects of COD, total lead, and color from wastewater. The nickel-ferrite composite magnetized cellulose flocculant prepared in the examples shows better performance than conventional flocculants such as polyaluminum ferric silicate and polyferric sulfate for treating wastewater alone. Furthermore, the treatment effect was poor after replacing the acidification solution NaIO4 with HCl, possibly because HCl did not completely acidify the cellulose. Under optimal conditions (Example 5), the removal rates of COD, total lead, and color reached 74.56%, 91.53%, and 90.62%, respectively.

[0103] from Figure 1 The SEM images show that the particles form tight aggregates through flocculation, indicating that the material has high structural strength and stability, which is beneficial to improving overall performance. The material surface exhibits a uniform porous morphology with strong adsorption capacity. The high surface roughness increases the interfacial contact area, promotes flocculation efficiency, and also has high mechanical stability.

[0104] It can be seen that the nickel ferrite composite magnetized cellulose flocculant provided by the present invention has mild reaction conditions, low cost, simple preparation, and excellent flocculation effect, and has a good market application prospect.

[0105] The contents described in this specification are merely an enumeration of the implementation forms of the inventive concept, and the scope of protection of this invention should not be regarded as limited to the specific forms described in the embodiments.

Claims

1. The application of a nickel-ferrite composite magnetized cellulose flocculant in the treatment of dyeing and printing wastewater, characterized in that, The flocculant is composed of the following components: Amine cellulose matrix: prepared by oxidation of cellulose with NaIO4, ammonia amination and reduction modification with NaBH3CN, and the surface is modified with hydroxyl-OH and amino-NH2 functional groups; NiFe2O4@SiO2, a nickel ferrite composite material, is formed by synthesizing NiFe2O4 from Fe salt and Ni salt under alkaline conditions via co-precipitation and then coating it with a SiO2 layer using a sol-gel method. Silane coupling agent bridging structure: The aminated cellulose matrix and NiFe2O4@SiO2 are covalently linked by 3-glycidyl etheroxypropyltrimethoxysilane KH560 to form an organic-inorganic hybrid network, which is the flocculant. The mass ratio of the aminated cellulose to NiFe2O4@SiO2 is 2:1 to 1:

1.

2. The application according to claim 1, characterized in that: The mass ratio of the aminated cellulose to NiFe2O4@SiO2 is 4:

3.

3. The application according to claim 1, characterized in that, The preparation method of flocculant includes the following steps: (1) Cellulose oxidative amination: Cellulose was dispersed in softened water, NaIO4 solution was added, and the mixture was stirred at 50-60℃ for 6-8 h. After filtration and washing, oxidized cellulose was obtained. Oxidized cellulose was mixed with 37% ammonia water at a solid-liquid ratio of 1g:10~20mL, and NaBH3CN solution was added. The mixture was reacted at 70~95℃ for 12~15 h. During the reaction, the mixture was cooled and refluxed to prevent ammonia from evaporating, thus obtaining amination cellulose. (2) Preparation of NiFe2O4@SiO2: Trivalent Fe salt and divalent Ni salt were mixed in a molar ratio of 2 to 4:1 and coprecipitated in an aqueous solution of NaOH with a final concentration of 0.7-1.0 mol / L at room temperature for 0.5-2 h. After that, NiFe2O4 was obtained by centrifugation and washing. NiFe2O4 was dispersed in ethanol, ammonia and tetraethyl orthosilicate (TEOS) were added, and the mixture was stirred at 50-60℃ for 20-24 h to carry out the hydrolysis reaction of TEOS and coat the NiFe2O4 with a SiO2 layer. After centrifugation and washing, NiFe2O4@SiO2 was obtained after high-temperature calcination. (3) Flocculant compound: Aminated cellulose was dissolved in toluene, and KH560 and NiFe2O4@SiO2 were added. The mixture was heated under reflux for 10-15 h, and then filtered, washed, and dried to obtain the target flocculant.

4. The application according to claim 3, characterized in that: In step (1), the mass ratio of NaIO4 to cellulose is 0.2-0.4:1, and the mass ratio of NaBH3CN to oxidized cellulose is 0.05-0.1:

1. In step (2), the final concentration of ammonia in the TEOS hydrolysis reaction system is 4-8%, and the feed ratio of NiFe2O4 to TEOS is 8-12g:1mL. In step (3), the mass ratio of KH560 to aminated cellulose is 0.8-1.2:1, and the mass ratio of aminated cellulose to NiFe2O4@SiO2 is 1~2:

1.

5. The application according to claim 4, characterized in that: The mass ratio of aminated cellulose to NiFe2O4@SiO2 is 4:

3.

6. The application according to claim 3, characterized in that: The calcination temperature in step (2) is 700-800℃, and the heating temperature in step (3) is 70-80℃.

7. The application according to claim 1, characterized in that... The wastewater has a pH of 5-11, the flocculant dosage is 1.0-2.0 g / L, the treatment temperature is room temperature, the reaction time is 30-60 min, and the removal rates of COD, total lead and color are ≥70%, 85% and 85%, respectively.

8. The application according to claim 1, characterized in that... The initial COD of the dyeing and printing wastewater is ≤ 3000 mg / L, the color is ≤ 2000 times, and the total lead concentration is ≤ 2.0 mg / L.

Citation Information

Patent Citations

  • Preparation method of cellulose base water-insoluble or slightly-soluble drug slow release microspheres

    CN110339183A

  • Processes for the preparation of branched, water soluble cellulose products

    US4531000A